2018
DOI: 10.1038/s41590-018-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Human germinal center transcriptional programs are de-synchronized in B cell lymphoma

Abstract: Most adult B cell lymphomas originate from germinal center (GC) B cells, but it is unclear to what extent B cells in overt lymphoma retain the functional dynamics of GC B cells or are blocked at a particular stage of the GC reaction. Here we used integrative single-cell analysis of phenotype, gene expression and variable-region sequence of the immunoglobulin heavy-chain locus to track the characteristic human GC B cell program in follicular lymphoma B cells. By modeling the cyclic continuum of GC B cell transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
133
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 56 publications
18
133
1
1
Order By: Relevance
“…During affinity maturation and selection in the GC, B cells cycle between physically distinct light and dark zones. While we clearly identified LZ and DZ B cell populations in our scRNA-seq dataset, we also found that many GC B cells existed in a continuum between these two states (Figure 4A-B) similar to previous reports (Milpied et al, 2018), with the exception of the FCRL2/3 high and prePB clusters which existed as transcriptionally distinct states (Figures 2H and 4C). In addition to unique gene expression patterns, these two sub-populations of GC B cells also exhibit unique patterns of class switching, with prePB B cells in the GC more likely to express class-switched isotypes and FCRL2/3 high GC B cells more likely to retain expression of IgM and IgD (Figures 2I and 4D).…”
Section: Resultssupporting
confidence: 90%
“…During affinity maturation and selection in the GC, B cells cycle between physically distinct light and dark zones. While we clearly identified LZ and DZ B cell populations in our scRNA-seq dataset, we also found that many GC B cells existed in a continuum between these two states (Figure 4A-B) similar to previous reports (Milpied et al, 2018), with the exception of the FCRL2/3 high and prePB clusters which existed as transcriptionally distinct states (Figures 2H and 4C). In addition to unique gene expression patterns, these two sub-populations of GC B cells also exhibit unique patterns of class switching, with prePB B cells in the GC more likely to express class-switched isotypes and FCRL2/3 high GC B cells more likely to retain expression of IgM and IgD (Figures 2I and 4D).…”
Section: Resultssupporting
confidence: 90%
“…The expression levels of surface protein markers recorded through index sorting were consistent with the gating strategy of Mem B cells (CD20 + CD38 lo CD10 -CD27 + ), GC B cells (CD20 + CD38 + CD10 + ) and PB/PCs (CD38 hi CD27 hi ) (Figure 4A Figure 4B), and identified the top marker genes for each cell subset ( Figure 4C). Those analyses were consistent with previous single-cell qPCR analyses 17 and bulk microarray analyses of human B cell subsets 27,28 .…”
Section: Fb5p-seq Analysis Of Human Tonsil B Cell Subsetssupporting
confidence: 90%
“…The progeny of a single T or B cell can thus be accurately identified through identical (for TCR) or very similar (for BCR) V-J junctional sequences in their TCR or BCR chain genes, respectively. Integrating single-cell immunoglobulin heavy chain (IGH) sequencing with lowthroughput gene expression analysis by single-cell qPCR already revealed important features of memory B cell diversification 16 and B cell lymphoma evolution 17 . Methods which enable parallel analysis of repertoire sequence and whole transcriptome gene expression in single B or T cells are required to deeply investigate multiple aspects of lymphocyte biology and malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…3C). In the tumor biopsy from a freshly diagnosed follicular lymphoma (FL) (36), n = 13 γδ T lymphocytes of 472 TILs (3.3%) were detected ( Fig. 3D and SI Appendix, Fig.…”
Section: A Gene Signature To Detect Human γδ T Lymphocytes In Complexmentioning
confidence: 99%